Dousing the flames of hatred - Abd Razak, Dzulkifli (2009)
THE number of people who perished in the devastating Black Saturday bush fires that continue to rage in southeastern Australia has exceeded 200. More bodies are expected to be found as police comb the area for evidence that may help to identify those caught in the fire. The Australian government has announced there will be a national day of mourning today to honour the victims of what is the worst wildfire in the country's recent history. Sources are relating how the fires quite literally flew from one spot to another almost spontaneously. That the temperature stands at close to 50 degree Celsius is fuelling it further.